Bolting reliability for offshore oil and natural gas operations : proceedings of a workshop - Johnson, Anne Frances (The National Academies Press, 2018)
"The Planning Committee on Connector Reliability for Offshore Oil and Natural Gas Operations held the Workshop on Bolting Reliability for Offshore Oil and Natural Gas Operations in Washington, D.C., on April 10-11, 2017. The workshop was designed to advance and develop a comprehensive awareness of the outstanding issues associated with fastener material failures and equipment reliability issues. Speakers and participants were also encouraged to discuss possible paths for ameliorating risks associated with fasteners used for subsea critical equipment in oil and gas operations. This publication summarizes the presentations and discussions from the workshop"--Publisher's description